Survey of the New Madrid, Mo., area - Walker, John, active 1788-1789.
Survey of the area around New Madrid, Mo.
Surveyor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: New Madrid (Mo.) -- Surveys; Surveyors